2001
DOI: 10.2337/diabetes.50.3.667
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipid Peroxidation Restores Impaired Vascular Endothelial Growth Factor Expression and Stimulates Wound Healing and Angiogenesis in the Genetically Diabetic Mouse

Abstract: Impaired wound healing is a well-documented phenomenon in experimental and clinical diabetes. Experimental evidence suggests that a defect in vascular endothelial growth factor (VEGF) regulation might be associated with wound-healing disorders. We studied the involvement of lipid peroxidation in the pathogenesis of altered VEGF expression in diabetes-related healing deficit by using an incisional skin-wound model produced on the back of female diabetic C57BL/KsJ db؉/ db؉ mice and their normal (db؉/؉m) litterma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(197 citation statements)
references
References 30 publications
8
188
0
1
Order By: Relevance
“…The overproduction of free radicals in diabetes could also cause an impairment in the production and release of the powerful angiogenic factor VEGF. Experimental evidence from our laboratory have indicated that in genetically diabetic mice the mRNA levels of VEGF as well as the wound content of the mature angiogenic factor were severely reduced during the healing process [18]. Furthermore lipid peroxidation inhibition restored wound healing to nearly normal levels and normalized the defect in VEGF regulation associated with diabetes-induced skin-repair disorders [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overproduction of free radicals in diabetes could also cause an impairment in the production and release of the powerful angiogenic factor VEGF. Experimental evidence from our laboratory have indicated that in genetically diabetic mice the mRNA levels of VEGF as well as the wound content of the mature angiogenic factor were severely reduced during the healing process [18]. Furthermore lipid peroxidation inhibition restored wound healing to nearly normal levels and normalized the defect in VEGF regulation associated with diabetes-induced skin-repair disorders [18].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate well-formed from poorlyformed capillary vessels the following parameters were considered: presence or absence of oedema, congestion, haemorrhage, thrombosis and intravascular or intervascular fibrin formation. The histological score adopted in this study was evaluated according to data regarding wound healing in experimental models [18,33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Alternatively, growth factor production might be impaired at the gene expression level, as we have recently observed for VEGF in the genetically diabetic mouse. 16 Given these considerations, it stems evident that a reasonable approach to alter the microenvironment of the wounded tissue and to stimulate wound healing is the topical application of growth factors. Although the results in animal studies are encouraging in this respect, 17 topical treatment with growth factors in the clinical setting is limited by several factors, such as their short half-lives, their inactivation by wound proteases, their poor bioavailability from the utilized vehicles, and the consequent need for daily applications and high initial doses that might result in toxicity.…”
Section: Healing Is Concomitant With An Increase Of Production Of Andmentioning
confidence: 99%
“…The histological score adopted in this study was evaluated according to literature data regarding wound healing in experimental models. 16 Immunohistochemistry Wounds collected at days 10 and 21 were fixed in 2% formaldehyde, embedded in paraffin, sectioned at 5 m thickness and mounted on to slides. Rehydrated serial paraffin sections were immersed in Tissue Unmasking Solution (Vector Laboratories, Burlingame, CA, USA) to reactivate hidden or masked epitopes and then placed in a microwave for 7 min at 350 W. Endogenous peroxidase activity was blocked with 3% hydrogen peroxide for 5 min.…”
Section: Histological Evaluationmentioning
confidence: 99%